Variability and motion of the Brazil-Malvinas front - Bianchi, Alejandro A. (1997)
The temporal evolution of the thermal field associated with frontal motions in the South Western Atlantic is studied. The analysis is based on data collected with an array of inverted echo sounders (IES) deployed during the Confluence Program (1988-1990) at the Brazil/Malvinas Confluence. The travel time series obtained with the IES are scaled to mean temperatures of the upper 500 m (Tsoo) of the ocean and series of T500 horizontal distributions are constructed. A description of the evolution of the thermal field, emphasizing the frontal motions and some mesoscaie features, is presented. Three well-defined northward penetrations of the Malvinas current with fairly variable periods of permanence (15-60 days) and mean frontal motion velocities of 0.2 m/s are observed. Cross-correlation of the T500 time series analysis leads to a plausible explanation of some features of the observed variability. Comparison with previous results in the area indicate a marked interannual variability and sources of variability are discussed.